AS RELAÇÕES ENTRE BEM-ESTAR NO TRABALHO E PARTICIPAÇÃO EM PROGRAMAS ORGANIZACIONAIS DE PROMOÇÃO DA SAÚDE - Basílio, Maria Aparecida (2005)
Presently, the keynote in the scientific field is the search for a better understanding of wellbeing at work; it gathers researchers of different fields, who have demonstrated interest in the subject. In a corporate context, programs that promote health and quality of life acquire an important role when employee productivity and well-being are to be improved, whereas it is essential for the company to obtain growing results in order to have permanent improvements of the work conditions, organization and relationships. In other words, companies understand that by investing in these programs productivity should increase, generating resources that would encourage them to continue investing in employee well-being. This study s goal was to analyze the relationship between well-being at work - represented by job satisfaction, job involvement and affective commitment to the organization and participation in organizational health promotion programs. The sample size was of 117 workers (53 males and 64 females) of a multinational chemical and pharmaceutical company in the Greater São Paulo region, aged on average 30.28 years, 63 of which were single, 46 married and eight reported another marital status. The instrument used to develop this study was a survey consisting of four scales that measured job satisfaction, job involvement, affective commitment to the organization and frequency of participation in health promotion programs conducted by the company. All data collected by this instrument was numeric in nature, which allowed it to be analyzed through SPSS, version 13.0 for Windows. This data category includes information on sample description, well-being at work and participation in health promotion programs. A database was created in order to conduct descriptive analysis (frequencies, percentage distribution, means and standard deviations) and bivariate correlation (Pearson s correlation coefficient r). The data that allowed describing the health promotion programs carried out by the company were obtained by interviewing the social responsibility manager, analyzing the company report and brochures made to disclose and register these programs. A total of five program categories were identified: benefits, physical activities, health, cultural/leisure activities and community actions. The highest program adherence rate occurred in the benefits category due to the constant presence of the restaurant on the company s premises. This study revealed that, to a large extent, well-being at work - especially as far as job involvement, affective commitment to the organization, as well as satisfaction regarding co-workers, superiors and the job itself are concerned is practically not affected by health promotion programs implemented by the company. On the other hand, the participation in health promotion programs, which include the benefits, health and community actions categories, was related to promotion and salary satisfaction